Nowa humanistyka służebna - Pertek, Grzegorz (Przestrzenie Teorii, 2023)
The paper is devoted to the theoretical foundation of the new humanities that have been recently developing in Poland. They result mainly from the need to surpass the theoretical and methodological horizon that was outlined by modern theory, especially by structuralism. The author argues that the more the new humanities attempt to revoke the modern theory, the more they are faithful to its premises. By analyzing the latest works of Ryszard Nycz, one of the main founders of the theoretical bases of the new humanities in Poland, the author shows i.a. how the main concepts of the main theory (in this case – mainly the concept of sounding out) work at its behalf.